PENGARUH MOTIVASI, KEPUASAN KERJA DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA BNI KANTOR CABANG SEMARANG - Agung Wijanarko, 09.05.51.0011 (Students Journal of Economic and Management, 2016)
Each company has a desire to improve and develop the business in ways that are arranged in a program to improve employee performance. In order to improve the performance, so that employees can work on target companies, ultimately enabling the company to compete with other companies. As for which is used as a population are all employees of BNI Semarang branch office numbering 77 employees. Sample selection technique using the method Purpose Sampling. The analysis tool used is multiple linear regression. The results showed that There is a positive and significant effect of motivation on employee performance There is a positive and significant impact on the performance of the employee job satisfaction There is a positive and significant influence on employee performance discipline Keywords: motivation, job satisfaction and work discipline on employee performance